2013
DOI: 10.1038/jcbfm.2012.179
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 Mediates Hyperbaric Oxygen Preconditioning-Induced Ischemic Tolerance in Rat Brain

Abstract: Our previous studies have shown that hyperbaric oxygen preconditioning (HBO-PC) induces tolerance to cerebral ischemia/reperfusion (I/R). This study aimed to investigate whether SirT1, a class III histone deacetylase, is involved in neuroprotection elicited by HBO-PC in animal and cell culture models of ischemia. Rats were subjected to middle cerebral artery occlusion for 120 minutes after HBO-PC (once a day for 5 days). Primary cultured cortical neurons were exposed to 2 hours of HBO-PC after 2 hours of oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 40 publications
(61 reference statements)
2
93
0
Order By: Relevance
“…Resveratrol-mediated neuroprotection was lost in the presence of sirtinol, confirming a role for SIRT1 in resveratrolmediated ischemic neuroprotection [38,39]. Using a different model of preconditioning, Yan et al [40] demonstrated that hyperbaric oxygen preconditioning increased SIRT1 protein [38] expression and that inhibition of SIRT1 deacetylase activity with EX527 blocked hyperbaric oxygen preconditioning neuroprotection against MCAO-mediated damage. It is interesting to note that transgenic mice overexpressing neuronalspecific SIRT1 are not protected against ischemic damage, suggesting that other signaling pathways may work in conjunction with SIRT1 for the induction of ischemic tolerance [41].…”
Section: Acetylationmentioning
confidence: 94%
“…Resveratrol-mediated neuroprotection was lost in the presence of sirtinol, confirming a role for SIRT1 in resveratrolmediated ischemic neuroprotection [38,39]. Using a different model of preconditioning, Yan et al [40] demonstrated that hyperbaric oxygen preconditioning increased SIRT1 protein [38] expression and that inhibition of SIRT1 deacetylase activity with EX527 blocked hyperbaric oxygen preconditioning neuroprotection against MCAO-mediated damage. It is interesting to note that transgenic mice overexpressing neuronalspecific SIRT1 are not protected against ischemic damage, suggesting that other signaling pathways may work in conjunction with SIRT1 for the induction of ischemic tolerance [41].…”
Section: Acetylationmentioning
confidence: 94%
“…Under chloral hydrate anesthesia, focal cerebral ischemia was performed using the method of right MCAO with an intraluminal filament as described previously [13]. Cerebral blood flow (CBF) was monitored using laser Doppler flowmetry (Perimed AB, PeriFlux System 5000, Stockholm, Sweden) in the ipsilateral cortex (2 mm posterior and 5 mm lateral to the bregma).…”
Section: Middle Cerebral Artery Occlusion Modelmentioning
confidence: 99%
“…The upregulation of the HDAC SIRT1 has been described to confer protection in stroke. 72 However, histone acetylation levels are not considered in this study and SIRT1 is known to have a wide range of non-histone targets 73 that constitute potential mediators of the protective effect. Interestingly, in a genome-wide association study for ischemic stroke, carried out in humans by the International Stroke Genetics Consortium and the Welcome Trust Case Control Consortium2, a new association has been identified between HDAC 9 and large vessel stroke, one of the brain infarct subtypes.…”
Section: Dna Methylationmentioning
confidence: 99%